The effects of harsh aging environments on the properties of neat and MWCNT reinforced epoxy resins. (22nd February 2021) - Aslan, Abdullah; Salur, Emin; Düzcükoğlu, Hayrettin; Sinan Şahin, Ömer; Ekrem, Mürsel
Highlights: Epoxy resins were affected mechanically and chemically from corrosive environment significantly. While the acidic environment aging adversely effects the properties of epoxy resin, it is determined that salty water environment aging increase the strength of epoxy resin. The MWCNT nano particles reinforcement diminish the endurance of epoxy resin against the aging environment. Abstract: In this study, the effects of different harsh aging environments on the chemical and mechanical properties of neat and multiwall carbon nanotubes (MWCNT) reinforced epoxy resins were investigated. The neat and 1 wt% MWCNT reinforced epoxy resins were exposed to four different corrosive environments, namely deionized water, NaCl solution (10 wt% NaCl), H2 SO4 solution (10 wt% H2 SO4 ), and HCl solution (10 wt% HCl. The mass variation results revealed that the highest absorption rates were found in specimens aged in both acidic environments. The highest amount of absorption was observed in the H2 SO4 environment, measured approximately 3% for neat epoxy, and 6.5% for MWCNT reinforced epoxy resin. FT-IR spectrums showed that the most affected peaks belong to specimens aged in both acidic environments. Tensile test results revealed that the aging process in H2 SO4 solution and deionized water deteriorated the strength of specimens. According to the literature, it was reported that the strength of specimens aged in NaCl solution environment is decreased. However, the same trend has not been in this study. In our study, the strength of specimens aged in NaCl solution environment increased impressively by 29%, which makes this study more striking. Another important point analyzed from the tensile test results was that the MWCNT nanoparticle reinforcement adversely affects the strength of the epoxy resin. So, it can be clearly stated that the use of expensive MWCNTs as filler of epoxy resin is not useful to improve its aging resistance. The scanning electron microscope (SEM) and optical microscope images showed that acidic environments result in different fracture mechanisms from typical polymer damaged surfaces reported in available researches.